Mental Health Identification Practices of Jails: The Unmet Needs of the "Silent" Population: Special Issue: Criminal Justice and Community Psychology: Our Values and Our Work. Issue 1 (3rd October 2020) - Comartin, Erin B.; Milanovic, Edita; Nelson, Victoria; Kubiak, Sheryl
Abstract: The overrepresentation of individuals with mental illness in the criminal/legal system is well documented. While professional associations urge diversion towards treatment, little is known about the practices these institutions use to identify this population. One understudied space in the criminal/legal continuum is jails. This exploratory study compares two types of mental health identification at jail booking to assess jail‐ and community‐based service outcomes by identification type ( N = 2956): (a) staff observation and (b) a standardized screening instrument. Individuals identified through staff observation were significantly more likely to receive jail‐ and community‐based services, even though current symptomology and substance misuse were both significantly higher for individuals identified only by the screening instrument. These findings point to the importance of jails in providing stabilizing services during incarceration, but further, show the impact that identification practices have on individuals as they transition to the community. Community context showed varied rates of jail staff observations of mental illness, showing greater risks for individuals in rural communities. Implications include a need for system‐level changes by instituting evidence‐based identification practices in jails, and improving professional collaboration practices between mental health and criminal/legal practitioners as individuals enter and exit jails. Highlights: This study compares the mental health identification practices‐as‐usual (i.e. staff observation) of eight jails to an objective screening instrument, and assesses the jail‐ and community‐based service outcomes resulting from these methods. Individuals identified by staff observation were significantly more likely to receive jail‐ and community‐based services, even though those identified by only the screening instrument had significantly greater behavioral health risks. Rural jails were significantly less likely to identify individuals through staff observation, yet had higher proportions identified by the screening instrument. Mental health practices of jails can have enduring treatment effects that follow individuals as they return to the community. Staff training combined with a screening instrument is recommended for identification, as well as strong community‐based collaborations for uninterrupted care upon reentry.